Technical manual for high-quality and low-emission rice production in the Mekong River Delta - Department of Crop Production (2024)
The 1 million ha technical manual provides guidelines for sustainable rice production, focusing on cultivation techniques, harvest and post-harvest management, and straw management. It emphasizes practices like water management, mechanized land preparation, alternate wetting and drying, and integrated pest management to reduce greenhouse gas emissions and improve rice quality. Additionally, the manual promotes efficient straw management through techniques like chopping and incorporating straw with Tricoderma spraying and avoiding open-field burning.